HIDRO-BIOLOGI LARVA IKAN DALAM PROSES REKRUTMEN - Amarullah, Muhammad Husni (Jurnal Hidrosfir Indonesia, 2008)
Prior understanding of stock dynamics of adult fishes were unable to fully explain observed variability in stock size. It was realized that variable “year- class success” was most likely determined during early (larval-juvenile stages) in marine fishes. Survival of individuals at any stage of life requires adequate levels of performance against a variety of ecological challenges, such as obtaining food, evading predators and locating and remaining in suitable habitat. Knowledge of processes that strongly affect larval survival would provide early evidence of the abundance of the emerging year class.